TMT proteomics analysis of a pseudocereal crop, quinoa (Chenopodium quinoa Willd.), during seed maturation - Shen, Zhi-Jun; Xu, Su-Xia; Huang, Qing-Yun; Li, Zi-Yang; Xu, Yi-Ding; Lin, Chun-Song; Huang, Yi-Jin (Frontiers in Plant Science, 2022)
Quinoa (Chenopodium quinoa Willd.), an Andean native crop, is increasingly popular around the world due to its high nutritional content and stress tolerance. The production and popularity of this strategic global food are greatly restricted by many limiting factors, such as seed pre-harvest sprouting, bitter saponin, etc. To solve these problems, the underlying mechanism of seed maturation in quinoa needs to be investigated. In this study, based on the investigation of morphological characteristics, a quantitative analysis of its global proteome was conducted using the combinational proteomics of TMT labeling and parallel reaction monitoring (PRM). The proteome changes related to quinoa seed maturation conversion were monitored to aid its genetic improvement. Typical changes of morphological characteristics were discovered during seed maturation including mean grain diameter, mean grain thickness, mean hundred-grain weight, palea, and episperm color, etc. With TMT proteomics analysis, 581 differentially accumulated proteins (DAPs) were identified. Functional classification analysis and GO enrichment analysis showed that most DAPs involved in photosynthesis were down-regulated, indicating low levels of photosynthesis. DAPs participated in glycolysis, such as glyceraldehyde-3-phosphate dehydrogenase, pyruvate decarboxylase, and alcohol dehydrogenase, were up-regulated to fulfill the increasing requirement of energy consumption during maturation conversion. The storage proteins, such as globulins, legumins, vicilins, and oleosin were also increased significantly during maturation conversion. Protein-protein interaction analysis and function annotation revealed that the up-regulation of oleosin, oil body-associated proteins, and acyl-coenzyme A oxidase 2 resulted in the accumulation of oil in quinoa seeds. The down-regulation of β-amyrin 28-oxidase was observed, indicating the decreasing saponin content, during maturation which makes quinoa “sweet”. By the PRM and qRT-PCR analysis, the expression patterns of most selected DAPs were consistent with the result of TMT proteomics. Our study enhanced the understanding of the maturation conversion in quinoa. This might be the first and most important step toward the genetic improvement of quinoa.